ANALISIS GENDER PENERAPAN PERATURAN PENCEGAHAN KEKERASAN SEKSUAL DI PERGURUAN TINGGI DI INDONESIA - Abd Hannan (Universitas Islam Negeri Imam Bonjol Padang, 2022)
This study examines the application of regulations to prevent sexual violence in universities from a gender perspective. There are two research questions examined in this study, how are the dynamics of violence and sexual harassment in the campus environment in Indonesia? How is the implementation of regulations and prevention of sexual violence in universities in Indonesia, from a gender perspective? Methodologically, this study uses a qualitative research type. The data in this study consisted of primary data and secondary data. By using an in-depth analysis based on the sociological theory of gender, this study found two findings; First, one of the crucial issues currently engulfing universities in Indonesia is the proliferation of acts of violence and sexual harassment. There are many factors why cases of sexual crimes on campuses in Indonesia are high, one of the most dominant is the imbalance of power relations at the level of the academic community, between students and elements of the campus community, especially with lecturers. Second, in the perspective of gender sociology, the problems that trigger sexual crimes on campuses in Indonesia can be grouped into two; gender differences that are based on dichotomous views such as patriarchy and the like, as well as gender inequality caused by the unequal distribution of resources at the institutional level. To be able to solve it, it is necessary to have special legislation that explicitly and clearly regulates sexual crimes on campus. In this regard, the application of the Permendikbud No 30 Tahun 2021 concerning the Prevention and Handling of Sexual Violence (PPKS) in Higher Education contains significant functions and roles in suppressing and minimizing or even eradicating, sexual crimes on campus.